A Predictive Model of Plasma Lamotrigine Levels - Kamei, K.; Terao, T.; Katayama, Y.; Hatano, K.; Kodama, K.; Shirahama, M.; Sakai, A.; Hirakawa, H.; Mizokami, Y.; Shiotsuki, I.; Ishii, N.; Inoue, Y. (Pharmacopsychiatry, 2016)
Introduction: Lamotrigine is one of several mood stabilizers and its effects for the treatment and prevention of depressive episodes, particularly in bipolar disorder, are generally accepted. Although the findings about a therapeutic window of lamotrigine are yet to be determined, it seems important to obtain information on individual pharmacokinetic peculiarities. This study was conducted to formulate the predictive model of plasma lamotrigine levels.Methods: Using the data of 47 patients whose lamotrigine levels, liver function, and renal function were measured, predictive models of lamotrigine levels were formulated by stepwise multiple regression analyses. The predictive power of the models was compared using another dataset of 25 patients.Results: Two models were created using stepwise multiple regression. The first model was: plasma lamotrigine level (μg/mL)=2.308+0.019×lamotrigine dose (mg/day). The second model was: plasma lamotrigine level (μg/mL)=0.08+0.024×lamotrigine dose (mg/day)+4.088×valproate combination (no=0, yes=1). The predictive power of the second model was better than that of the first model.Discussion: The present study proposes a prompt and relatively accurate equation to predict lamotrigine levels.
Keywords: lamotrigine; plasma levels; prediction; valproate